Preparation method of multistage submicron silicon negative electrode material for lithium ion battery

By using a carbon aerogel to wrap micron silicon in lithium-ion batteries, the volume expansion problem of micron silicon is solved, the cycle performance stability is improved, and the battery performance with high energy density and long life is achieved .

CN119230792AActive Publication Date: 2024-12-31SHAOXING INST OF QUALITY & TECH SUPERVISION & INSPECTION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411510895.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-31
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Micron silicon has serious volume expansion problems in lithium-ion batteries, resulting in reduced cycle life, and the high cost and low consistency of nano-silicon are difficult to meet the needs of scale.

Method used

The preparation method of multi-stage negative electrode material with carbon aerogel wrapped in micron silicon is formed through surface modification, ultrasonication, lyophilization and carbonization treatment to form a high-porous carbon aerogel structure to achieve conductive connectivity and compressibility and alleviate Volume expansion effect and improve cyclic performance stability.

Benefits of technology

It effectively solves the expansion problem of micron silicon, improves the stability of cycle performance, meets the needs of high-energy-density lithium-ion batteries, and realizes the long life and efficient energy storage of micron silicon negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105429050000091
    Figure BDA0005105429050000091
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a preparation method of a multistage submicron silicon negative electrode material for a lithium ion battery, the micron silicon negative electrode material takes micron silicon as an inner core, takes carbon aerogel as a connecting layer, and takes a polypyrrole-ethyl cellulose based carbon layer as a surface layer; the invention also provides preparation steps of the micron silicon negative electrode material. The problem of expansibility of existing micron silicon is solved, conductive connection between a surface carbon layer and the micron silicon is achieved by means of compressibility and conductivity of the carbon aerogel, meanwhile, compressible pores are formed by means of the carbon aerogel of a high-pore structure, enough expansion space is given to the micron silicon, and the cycle performance stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for preparing a multi-level sub-micron silicon negative electrode material for lithium ion batteries. Background Art

[0002] As people pay more attention to environmental protection and new energy technologies develop rapidly, the trend of electric vehicles powered by new energy gradually replacing traditional fuel vehicles has gradually been accepted by people. As the most advantageous, technologically mature and commercialized energy storage system, lithium-ion batteries have been widely used in electric vehicles. With the popularity of such electric vehicles and the continuous improvement of the quality of life, people's demand for long-range electric vehicles continues to grow, and high-density lithium-ion batteries have become one of the main research areas in the field of new energy.

[0003] Silicon reacts with lithium ions to form lithium-silicon alloy, which has an ultra-high theoretical capacity of up to 3579mAh / g, which is ten times that of graphite negative electrode. At the same time, silicon is abundant, widely present in nature, and has low production cost. Therefore, it is considered one of the most competitive negative electrode materials for high energy density lithium-ion batteries. However, silicon-based negative electrodes have serious volume expansion problems during the charging and discharging process. The volume expansion rate exceeds 300%, which will destroy the surface film structure of the negative electrode material and cause the active material to pulverize and detach, ultimately affecting the electrode cycle life and causing battery failure. Although nano-silicon can alleviate the volume expansion problem of silicon materials to a certain extent, its high manufacturing cost, low tap density, and poor consistency have caused nano-silicon to be not widely used and difficult to meet the requirements of scale. Micron silicon can circumvent the defects of high cost, low tap density, and poor consistency of nano-silicon, but it has the disadvantages of severe volume expansion effect and rapid cycle decay.

[0004] Therefore, the market urgently needs a micron silicon negative electrode material that can alleviate the volume expansion effect and has stable cycle performance. Summary of the invention

[0005] In view of the problems in the prior art, the present invention provides a method for preparing a multi-level sub-micron silicon negative electrode material for lithium-ion batteries, which solves the expansion problem of existing micron silicon. The compressibility and conductivity of carbon aerogel itself are utilized to achieve conductive connectivity between the surface carbon layer and the micron silicon. At the same time, compressible pores are formed by using carbon aerogel with a high porosity structure, which gives the micron silicon sufficient expansion space and improves the stability of cycle performance.

[0006] In order to achieve the above technical objectives, the technical solution of the present invention is:

[0007] A method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery comprises the following steps:

[0008] Step 1, putting the micron silicon material into an ethanol aqueous solution and stirring it evenly, then adding a hydrochloric acid solution for surface modification to obtain activated micron silicon, wherein the concentration of the micron silicon material in the ethanol aqueous solution is 20-50 g / L, the volume proportion of ethanol in the ethanol aqueous solution is 50-70%, the stirring speed for the even stirring is 300-500 r / min, and the temperature is 10-20° C.; the pH of the hydrochloric acid solution is 4-5, and the volume ratio of the hydrochloric acid solution to the ethanol aqueous solution is 1:(1.5-2), the surface modification temperature is 20-30° C., and the stirring speed is 200-300 r / min. This step utilizes the cleaning effect of the ethanol aqueous solution to remove impurities on the surface of the micron silicon and realize crystallization of the micron silicon surface. During the addition of hydrochloric acid, the ethanol aqueous solution is converted into an acidic ethanol aqueous solution, thereby achieving acid activation of the micron silicon surface;

[0009] Step 2, putting hydroxyethyl cellulose and ethyl cellulose into an ethanol aqueous solution and stirring them evenly to form a mixed solution, then stirring the activated micron silicon, ultrasonically filtering and freeze-drying to obtain cellulose aerogel-wrapped micron silicon, the mass ratio of the hydroxyethyl cellulose and ethyl cellulose is 3:(1-1.2), the mass ratio of the hydroxyethyl cellulose to the ethanol aqueous solution is 1:(2-3), the volume proportion of ethanol in the ethanol aqueous solution is 15-20%, the stirring speed for uniform stirring is 100-200r / min, the mass ratio of the activated micron silicon to the hydroxyethyl cellulose is 1:(0.8-1.1), the stirring speed is 200-400r / min, the frequency of the ultrasound is 80-100kHz, the temperature is 20-30°C; the freeze-drying temperature is -20°C; this step utilizes the solubility of hydroxyethyl cellulose and ethyl cellulose in the ethanol aqueous solution to form a stable solution, utilizes stirring and ultrasonication to add micron silicon and form a liquid film on the surface of micron silicon, and forms a composite cellulose aerogel of ethyl cellulose and hydroxyethyl cellulose on the basis of freeze drying;

[0010] Step 3, soaking the cellulose aerogel-wrapped micron silicon in ether, stirring for 20-30 minutes, filtering, drying, and carbonizing to obtain carbon aerogel-wrapped micron silicon, wherein the mass ratio of the cellulose aerogel-wrapped micron silicon to ether is 1:(5-8), the stirring speed is 200-400r / min, the drying temperature is 50-60°C, the carbonization atmosphere is a nitrogen atmosphere, and the temperature is 230-250°C; in this step, the solubility change of hydroxyethyl cellulose and ethyl cellulose in ether is utilized during the ether soaking to achieve the purpose of removing ethyl cellulose, and obtain The structure of micron silicon is wrapped by hydroxyethyl cellulose aerogel, and then the hydroxyethyl cellulose is carbonized into carbon aerogel during the carbonization process. It should be noted that hydroxyethyl cellulose and activated micron silicon can form a stable connection structure based on hydroxyl groups, which ensures that the carbon aerogel and micron silicon have good stability; the carbon aerogel not only forms a stable aerogel structure by freeze-drying, but also ethyl cellulose and hydroxyethyl cellulose form secondary pores, which further pore the aerogel to obtain a carbon aerogel with strong compressibility and high porosity, and the carbon aerogel is controllable;

[0011] Step 4, putting pyrrole monomer and ethyl cellulose into ether and stirring evenly to form a monomer soaking liquid, then putting carbon aerogel-wrapped micron silicon into it and soaking it for 1-2 minutes, filtering and drying to obtain pre-plated carbon aerogel-wrapped micron silicon, and finally soaking it in pyrrole monomer liquid and stirring it for 1-2 minutes, and drying it to obtain coated carbon aerogel-wrapped micron silicon, wherein the mass ratio of the pyrrole monomer to ethyl cellulose is (0.8-1.2):1, the mass ratio of the pyrrole monomer to ether is 1:(3-4), the mass ratio of the carbon aerogel-wrapped micron silicon to ether is 1:(2-2.5), and the drying temperature is 40-50°C; the mass ratio of the carbon aerogel-wrapped micron silicon to the pyrrole monomer liquid is 1:( 1-1.5), the mass ratio of pyrrole monomer to ether in the pyrrole monomer liquid is 1:1, and the drying temperature is 40-50°C; this step utilizes the viscous system of ethyl cellulose in ether to effectively reduce the penetration effect of the monomer soaking liquid on the surface of the carbon aerogel-wrapped micron silicon, that is, the pyrrole monomer and ethyl cellulose form a surface film on the surface of the carbon aerogel-wrapped micron silicon soaking liquid, and the ether is directly removed to form an ethyl cellulose-pyrrole composite film; on the basis of the existence of the composite film, the pyrrole monomer is deposited on the surface of the composite film, and the ether on the pyrrole monomer liquid is used to penetrate the ethyl cellulose, thereby ensuring the stable coverage and fixation of the pyrrole monomer, and effectively increasing the concentration of the pyrrole monomer on the outer surface;

[0012] Step 5, soak the coated carbon aerogel wrapped micron silicon in a hydrogen peroxide solution for 20-30 minutes, and react at a constant temperature for 1-2 hours to obtain a self-polymerized coated carbon aerogel wrapped micron silicon, and then filter and heat-treat it to obtain a multi-level sub-micron silicon negative electrode material, the hydrogen peroxide solution uses 30% hydrogen peroxide, and the hydrogen peroxide solution is adjusted to pH 4-5 by hydrochloric acid, the concentration of the coated carbon aerogel wrapped micron silicon in the hydrogen peroxide solution is 100-300g / L, the temperature of the constant temperature reaction is 40-50°C; the temperature of the heat treatment is 600-650°C, and the atmosphere is a nitrogen atmosphere. This step utilizes the soaking effect of the acidic hydrogen peroxide solution and the insolubility of pyrrole monomer and ethyl cellulose in water to form an in-situ self-polymerization reaction, thereby forming a polypyrrole surface layer on the surface, that is, an ethyl cellulose-polypyrrole composite film is formed on the surface of the carbon aerogel wrapped micron silicon; after carbonization treatment, a carbon shell is formed on the surface of the micron silicon.

[0013] The multi-level sub-micron silicon negative electrode material in step 5 has micron silicon as a core, carbon aerogel as a connecting layer, and a polypyrrole-ethylcellulose-based carbon layer as a surface layer.

[0014] It can be seen from the above description that the present invention has the following advantages:

[0015] 1. The present invention solves the expansion problem of existing micron silicon. It utilizes the compressibility and conductivity of carbon aerogel itself to achieve conductive connectivity between the surface carbon layer and micron silicon. At the same time, it utilizes the highly porous carbon aerogel to form compressible pores, giving micron silicon sufficient expansion space and improving the stability of cycle performance.

[0016] 2. The present invention utilizes the physical porosity of ethyl cellulose and the freeze-dried aerogel molding structure, and cooperates with carbonization treatment to form a carbon aerogel structure, which is not only compressible and recoverable, but also has sufficient compression space to meet the expansion requirements of micron silicon.

[0017] 3. The present invention utilizes the solubility of ethyl cellulose to achieve in-situ aerogel pore formation and secondary dissolution pore formation, forming secondary pore formation in the aerogel system, which effectively improves the high porosity and compressibility of the carbon aerogel. DETAILED DESCRIPTION

[0018] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention.

[0019] Example 1

[0020] A method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery comprises the following steps:

[0021] Step 1, placing the micron silicon material in an ethanol aqueous solution and stirring it evenly, then adding a hydrochloric acid solution for surface modification to obtain activated micron silicon, wherein the concentration of the micron silicon material in the ethanol aqueous solution is 20 g / L, the volume proportion of ethanol in the ethanol aqueous solution is 50%, the stirring speed for the uniform stirring is 300 r / min, and the temperature is 10°C; the pH of the hydrochloric acid solution is 4, and the volume ratio of the hydrochloric acid solution to the ethanol aqueous solution is 1:1.5, the temperature of the surface modification is 20°C, and the stirring speed is 200 r / min;

[0022] Step 2, putting hydroxyethyl cellulose and ethyl cellulose into an ethanol aqueous solution and stirring evenly to form a mixed solution, then stirring the activated micron silicon, ultrasonically, filtering and freeze-drying to obtain cellulose aerogel-wrapped micron silicon, the mass ratio of the hydroxyethyl cellulose and the ethyl cellulose is 3:1, the mass ratio of the hydroxyethyl cellulose to the ethanol aqueous solution is 1:2, the volume proportion of ethanol in the ethanol aqueous solution is 15%, the stirring speed for uniform stirring is 100 r / min, the mass ratio of the activated micron silicon to the hydroxyethyl cellulose is 1:0.8, the stirring speed is 200 r / min, the frequency of the ultrasound is 80 kHz, the temperature is 20-30°C; the freeze-drying temperature is -20°C;

[0023] Step 3, soaking the cellulose aerogel-wrapped micron silicon in ether, stirring for 20 minutes, filtering, drying, and carbonizing to obtain carbon aerogel-wrapped micron silicon, wherein the mass ratio of the cellulose aerogel-wrapped micron silicon to the ether is 1:5, the stirring speed is 200 r / min, the drying temperature is 50° C., the carbonization atmosphere is a nitrogen atmosphere, and the temperature is 230° C.;

[0024] Step 4, putting pyrrole monomer and ethyl cellulose into ether and stirring evenly to form a monomer soaking liquid, then putting carbon aerogel-wrapped micron silicon into it and soaking it for 1 minute, filtering and drying to obtain pre-plated carbon aerogel-wrapped micron silicon, and finally soaking it in pyrrole monomer liquid and stirring it for 1 minute, drying to obtain coated carbon aerogel-wrapped micron silicon, wherein the mass ratio of the pyrrole monomer to ethyl cellulose is 0.8:1, the mass ratio of the pyrrole monomer to ether is 1:3, the mass ratio of the carbon aerogel-wrapped micron silicon to ether is 1:2, and the drying temperature is 40°C; the mass ratio of the carbon aerogel-wrapped micron silicon to the pyrrole monomer liquid is 1:1, the mass ratio of the pyrrole monomer in the pyrrole monomer liquid to ether is 1:1, and the drying temperature is 40°C;

[0025] Step 5, soaking the coated carbon aerogel-wrapped micron silicon in a hydrogen peroxide solution for 20 minutes, reacting at a constant temperature for 1 hour, obtaining self-polymerized coated carbon aerogel-wrapped micron silicon, and then filtering and heat-treating it to obtain a multi-stage sub-micron silicon negative electrode material, the hydrogen peroxide solution uses 30% hydrogen peroxide, and the hydrogen peroxide solution is adjusted to pH 4 by hydrochloric acid, the concentration of the coated carbon aerogel-wrapped micron silicon in the hydrogen peroxide solution is 100 g / L, the temperature of the constant temperature reaction is 40°C; the temperature of the heat treatment is 600-650°C, the atmosphere is a nitrogen atmosphere, and the multi-stage sub-micron silicon negative electrode material has micron silicon as the core, carbon aerogel as the connecting layer, and a polypyrrole-ethylcellulose-based carbon layer as the surface layer.

[0026] Example 2

[0027] A method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery comprises the following steps:

[0028] Step 1, placing the micron silicon material in an ethanol aqueous solution and stirring it evenly, then adding a hydrochloric acid solution for surface modification to obtain activated micron silicon, wherein the concentration of the micron silicon material in the ethanol aqueous solution is 50 g / L, the volume proportion of ethanol in the ethanol aqueous solution is 70%, the stirring speed for the uniform stirring is 500 r / min, and the temperature is 20°C; the pH of the hydrochloric acid solution is 5, and the volume ratio of the hydrochloric acid solution to the ethanol aqueous solution is 1:2, the temperature of the surface modification is 30°C, and the stirring speed is 300 r / min;

[0029] Step 2, putting hydroxyethyl cellulose and ethyl cellulose into an ethanol aqueous solution and stirring evenly to form a mixed solution, then stirring the activated micron silicon, ultrasonically, filtering and freeze-drying to obtain cellulose aerogel-wrapped micron silicon, the mass ratio of the hydroxyethyl cellulose and ethyl cellulose is 3:1.2, the mass ratio of the hydroxyethyl cellulose to the ethanol aqueous solution is 1:3, the volume proportion of ethanol in the ethanol aqueous solution is 20%, the stirring speed for uniform stirring is 200r / min, the mass ratio of the activated micron silicon to the hydroxyethyl cellulose is 1:1.1, the stirring speed is 400r / min, the frequency of the ultrasound is 100kHz, the temperature is 30°C; the freeze-drying temperature is -20°C;

[0030] Step 3, soaking the cellulose aerogel-wrapped micron silicon in ether, stirring for 30 minutes, filtering, drying, and carbonizing to obtain carbon aerogel-wrapped micron silicon, wherein the mass ratio of the cellulose aerogel-wrapped micron silicon to the ether is 1:8, the stirring speed is 400 r / min, the drying temperature is 60° C., the carbonization atmosphere is a nitrogen atmosphere, and the temperature is 250° C.;

[0031] Step 4, putting pyrrole monomer and ethyl cellulose into ether and stirring evenly to form a monomer soaking liquid, then putting carbon aerogel-wrapped micron silicon into it and soaking it for 2 minutes, filtering and drying to obtain pre-plated carbon aerogel-wrapped micron silicon, and finally soaking it in pyrrole monomer liquid and stirring it for 2 minutes, and drying to obtain coated carbon aerogel-wrapped micron silicon, wherein the mass ratio of the pyrrole monomer to ethyl cellulose is 1.2:1, the mass ratio of the pyrrole monomer to ether is 1:4, the mass ratio of the carbon aerogel-wrapped micron silicon to ether is 1:2.5, and the drying temperature is 50°C; the mass ratio of the carbon aerogel-wrapped micron silicon to the pyrrole monomer liquid is 1:1.5, the mass ratio of the pyrrole monomer in the pyrrole monomer liquid to ether is 1:1, and the drying temperature is 50°C;

[0032] Step 5, soaking the coated carbon aerogel-wrapped micron silicon in a hydrogen peroxide solution for 30 minutes, reacting at a constant temperature for 2 hours to obtain self-polymerized coated carbon aerogel-wrapped micron silicon, then filtering and heat-treating it to obtain a multi-stage sub-micron silicon negative electrode material, the hydrogen peroxide solution uses 30% hydrogen peroxide, and the hydrogen peroxide solution is adjusted to pH 5 by hydrochloric acid, the concentration of the coated carbon aerogel-wrapped micron silicon in the hydrogen peroxide solution is 300g / L, the temperature of the constant temperature reaction is 50°C; the temperature of the heat treatment is 650°C, the atmosphere is a nitrogen atmosphere, and the multi-stage sub-micron silicon negative electrode material has micron silicon as the core, carbon aerogel as the connecting layer, and a polypyrrole-ethylcellulose-based carbon layer as the surface layer.

[0033] Example 3

[0034] A method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery comprises the following steps:

[0035] Step 1, putting the micron silicon material into an ethanol aqueous solution and stirring it evenly, then adding a hydrochloric acid solution for surface modification to obtain activated micron silicon, wherein the concentration of the micron silicon material in the ethanol aqueous solution is 40 g / L, the volume proportion of ethanol in the ethanol aqueous solution is 60%, the stirring speed for stirring evenly is 400 r / min, and the temperature is 15°C; the pH of the hydrochloric acid solution is 4, and the volume ratio of the hydrochloric acid solution to the ethanol aqueous solution is 1:1.8, the temperature of the surface modification is 25°C, and the stirring speed is 250 r / min;

[0036] Step 2, putting hydroxyethyl cellulose and ethyl cellulose into an ethanol aqueous solution and stirring evenly to form a mixed solution, then stirring the activated micron silicon, ultrasonically, filtering and freeze-drying to obtain cellulose aerogel-wrapped micron silicon, the mass ratio of the hydroxyethyl cellulose and ethyl cellulose is 3:1.1, the mass ratio of the hydroxyethyl cellulose to the ethanol aqueous solution is 1:2.5, the volume proportion of ethanol in the ethanol aqueous solution is 18%, the stirring speed for uniform stirring is 150r / min, the mass ratio of the activated micron silicon to the hydroxyethyl cellulose is 1:1, the stirring speed is 300r / min, the frequency of the ultrasound is 90kHz, the temperature is 25°C; the freeze-drying temperature is -20°C;

[0037] Step 3, soaking the cellulose aerogel-wrapped micron silicon in ether, stirring for 25 minutes, filtering, drying, and carbonizing to obtain carbon aerogel-wrapped micron silicon, wherein the mass ratio of the cellulose aerogel-wrapped micron silicon to the ether is 1:7, the stirring speed is 300 r / min, the drying temperature is 55° C., the carbonization atmosphere is a nitrogen atmosphere, and the temperature is 240° C.;

[0038] Step 4, putting pyrrole monomer and ethyl cellulose into ether and stirring evenly to form a monomer soaking liquid, then putting carbon aerogel-wrapped micron silicon into it and soaking it for 1 minute, filtering and drying to obtain pre-plated carbon aerogel-wrapped micron silicon, and finally soaking it in pyrrole monomer liquid and stirring it for 2 minutes, and drying to obtain coated carbon aerogel-wrapped micron silicon, wherein the mass ratio of the pyrrole monomer to ethyl cellulose is 1:1, the mass ratio of the pyrrole monomer to ether is 1:3, the mass ratio of the carbon aerogel-wrapped micron silicon to ether is 1:2, and the drying temperature is 45°C; the mass ratio of the carbon aerogel-wrapped micron silicon to the pyrrole monomer liquid is 1:1.2, the mass ratio of the pyrrole monomer in the pyrrole monomer liquid to ether is 1:1, and the drying temperature is 45°C;

[0039] Step 5, soaking the coated carbon aerogel-wrapped micron silicon in a hydrogen peroxide solution for 25 minutes, reacting at a constant temperature for 2 hours, obtaining self-polymerized coated carbon aerogel-wrapped micron silicon, and then filtering and heat-treating it to obtain a multi-stage sub-micron silicon negative electrode material, the hydrogen peroxide solution uses 30% hydrogen peroxide, and the hydrogen peroxide solution is adjusted to pH 4 by hydrochloric acid, the concentration of the coated carbon aerogel-wrapped micron silicon in the hydrogen peroxide solution is 200g / L, the temperature of the constant temperature reaction is 45°C; the temperature of the heat treatment is 630°C, the atmosphere is a nitrogen atmosphere, and the multi-stage sub-micron silicon negative electrode material has micron silicon as the core, carbon aerogel as the connecting layer, and a polypyrrole-ethylcellulose-based carbon layer as the surface layer.

[0040] Comparative Example 1

[0041] A method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery comprises the following steps:

[0042] Step 1, putting the micron silicon material into an ethanol aqueous solution and stirring it evenly, then adding a hydrochloric acid solution for surface modification to obtain activated micron silicon, wherein the concentration of the micron silicon material in the ethanol aqueous solution is 40 g / L, the volume proportion of ethanol in the ethanol aqueous solution is 60%, the stirring speed for stirring evenly is 400 r / min, and the temperature is 15°C; the pH of the hydrochloric acid solution is 4, and the volume ratio of the hydrochloric acid solution to the ethanol aqueous solution is 1:1.8, the temperature of the surface modification is 25°C, and the stirring speed is 250 r / min;

[0043] Step 2, putting conductive carbon black and ethyl cellulose into an ethanol aqueous solution and stirring evenly to form a mixed solution, then stirring the activated micron silicon, ultrasonically, filtering and freeze-drying to obtain cellulose aerogel-wrapped micron silicon, the mass ratio of the conductive carbon black and ethyl cellulose is 8:1, the mass ratio of the conductive carbon black to the ethanol aqueous solution is 1:2.5, the volume proportion of ethanol in the ethanol aqueous solution is 18%, the stirring speed for uniform stirring is 150r / min, the mass ratio of the activated micron silicon to hydroxyethyl cellulose is 1:1, the stirring speed is 300r / min, the frequency of the ultrasound is 90kHz, the temperature is 25°C; the freeze-drying temperature is -20°C;

[0044] Step 3, soaking the cellulose aerogel-wrapped micron silicon in ether, stirring for 25 minutes, filtering, drying, and carbonizing to obtain carbon aerogel-wrapped micron silicon, wherein the mass ratio of the cellulose aerogel-wrapped micron silicon to the ether is 1:7, the stirring speed is 300 r / min, the drying temperature is 55° C., the carbonization atmosphere is a nitrogen atmosphere, and the temperature is 240° C.;

[0045] Step 4, putting pyrrole monomer and ethyl cellulose into ether and stirring evenly to form a monomer soaking liquid, then putting carbon aerogel-wrapped micron silicon into it and soaking it for 1 minute, filtering and drying to obtain pre-plated carbon aerogel-wrapped micron silicon, and finally soaking it in pyrrole monomer liquid and stirring it for 2 minutes, and drying to obtain coated carbon aerogel-wrapped micron silicon, wherein the mass ratio of the pyrrole monomer to ethyl cellulose is 1:1, the mass ratio of the pyrrole monomer to ether is 1:3, the mass ratio of the carbon aerogel-wrapped micron silicon to ether is 1:2, and the drying temperature is 45°C; the mass ratio of the carbon aerogel-wrapped micron silicon to the pyrrole monomer liquid is 1:1.2, the mass ratio of the pyrrole monomer in the pyrrole monomer liquid to ether is 1:1, and the drying temperature is 45°C;

[0046] Step 5, soaking the coated carbon aerogel-wrapped micron silicon in a hydrogen peroxide solution for 25 minutes, reacting at a constant temperature for 2 hours, obtaining self-polymerized coated carbon aerogel-wrapped micron silicon, and then filtering and heat-treating it to obtain a multi-stage sub-micron silicon negative electrode material, the hydrogen peroxide solution uses 30% hydrogen peroxide, and the hydrogen peroxide solution is adjusted to pH 4 by hydrochloric acid, the concentration of the coated carbon aerogel-wrapped micron silicon in the hydrogen peroxide solution is 200g / L, the temperature of the constant temperature reaction is 45°C; the temperature of the heat treatment is 630°C, and the atmosphere is a nitrogen atmosphere.

[0047] Performance Testing

[0048] The negative electrode materials in Examples 1-3 and Comparative Example 1 are prepared to form negative electrode sheets, and the preparation method of the negative electrode sheets is: adding carboxymethyl cellulose into water and stirring evenly to form a glue solution, then adding the negative electrode material and lithium titanate in sequence, mixing into a slurry, coating the slurry on the surface of a conductive substrate, and drying to obtain a negative electrode sheet, wherein the mass ratio of carboxymethyl cellulose, lithium titanate, and negative electrode material is 1:0.5:10, the mass ratio of carboxymethyl cellulose to water is 1:40, the drying temperature is 110°C, and the drying time is 12h.

[0049] The negative electrode sheets prepared from the negative electrode materials prepared in Examples 1-3 and Comparative Example 1 were used as working electrodes and button cells were assembled with LiPF6 / DMC+EC+DEC (1:1:1) as the electrolyte. The charge and discharge were carried out with a cut-off voltage of 0.01-1.5V. The first charge specific capacity, first coulomb efficiency, 50-week cycle retention rate, and 0.3C / 0.1C capacity retention rate were measured. The test results are as follows.

[0050]

[0051] The above test data show that the micron silicon lithium battery negative electrode material prepared by this method has good performance, and performs well in the first charge specific capacity, first coulomb efficiency, 50-week cycle retention rate, and 0.3C / 0.1C capacity retention rate.

[0052] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery, characterized in that: The preparation method comprises the following steps: Step 1, placing the micron silicon material in an ethanol aqueous solution and stirring it evenly, then adding a hydrochloric acid solution for surface modification to obtain activated micron silicon; Step 2, adding hydroxyethyl cellulose and ethyl cellulose into an ethanol aqueous solution and stirring evenly to form a mixed solution, and then stirring the activated micron silicon, performing ultrasonication, filtering and freeze drying to obtain cellulose aerogel-encapsulated micron silicon; Step 3, soaking the cellulose aerogel-wrapped micron silicon in ether, stirring for 20-30 minutes, filtering, drying, and carbonizing to obtain carbon aerogel-wrapped micron silicon; Step 4, putting pyrrole monomer and ethyl cellulose into ether and stirring evenly to form a monomer soaking liquid, then putting carbon aerogel-wrapped micron silicon into it and soaking it for 1-2 minutes, filtering and drying to obtain pre-plated carbon aerogel-wrapped micron silicon, and finally soaking it in pyrrole monomer liquid and stirring it for 1-2 minutes, and drying it to obtain coated carbon aerogel-wrapped micron silicon; Step 5, soak the coated carbon aerogel wrapped micron silicon in a hydrogen peroxide solution for 20-30 minutes, react at a constant temperature for 1-2 hours to obtain self-polymerized coated carbon aerogel wrapped micron silicon, then filter and heat-treat it to obtain a multi-level sub-micron silicon negative electrode material.

2. The method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The concentration of the micron silicon material in the ethanol aqueous solution in step 1 is 20-50 g / L, the volume proportion of ethanol in the ethanol aqueous solution is 50-70%, the stirring speed for uniform stirring is 300-500 r / min, and the temperature is 10-20°C.

3. The method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The pH of the hydrochloric acid solution in step 1 is 4-5, and the volume ratio of the hydrochloric acid solution to the ethanol aqueous solution is 1:(1.5-2). The surface modification temperature is 20-30° C., and the stirring speed is 200-300 r / min.

4. The method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The mass ratio of hydroxyethyl cellulose to ethyl cellulose in step 2 is 3:(1-1.2), the mass ratio of hydroxyethyl cellulose to ethanol aqueous solution is 1:(2-3), the volume proportion of ethanol in the ethanol aqueous solution is 15-20%, and the stirring speed for uniform stirring is 100-200 r / min.

5. The method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The mass ratio of activated micro-silicon to hydroxyethyl cellulose in step 2 is 1:(0.8-1.1), the stirring speed is 200-400r / min, the frequency of the ultrasound is 80-100kHz, the temperature is 20-30°C; and the freeze-drying temperature is -20°C.

6. The method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The mass ratio of the cellulose aerogel-wrapped micron silicon to ether in step 3 is 1:(5-8), the stirring speed is 200-400 r / min, the drying temperature is 50-60°C, the carbonization atmosphere is a nitrogen atmosphere, and the temperature is 230-250°C.

7. The method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The mass ratio of pyrrole monomer to ethyl cellulose in step 4 is (0.8-1.2):1, the mass ratio of pyrrole monomer to diethyl ether is 1:(3-4), the mass ratio of carbon aerogel-wrapped micron silicon to diethyl ether is 1:(2-2.5), and the drying temperature is 40-50°C; the mass ratio of carbon aerogel-wrapped micron silicon to pyrrole monomer liquid is 1:(1-1.5), the mass ratio of pyrrole monomer in the pyrrole monomer liquid to diethyl ether is 1:1, and the drying temperature is 40-50°C.

8. The method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The hydrogen peroxide solution in step 5 uses 30% hydrogen peroxide, and the pH of the hydrogen peroxide solution is adjusted to 4-5 by hydrochloric acid. The concentration of the coated carbon aerogel-wrapped micron silicon in the hydrogen peroxide solution is 100-300 g / L, and the temperature of the isothermal reaction is 40-50°C.

9. The method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The heat treatment temperature in step 5 is 600-650° C., and the atmosphere is a nitrogen atmosphere.

10. The method for preparing a multi-level sub-micron silicon negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The multi-level sub-micron silicon negative electrode material in step 5 has micron silicon as the core, carbon aerogel as the connecting layer, and a polypyrrole-ethyl cellulose-based carbon layer as the surface layer.

Citation Information

Patent Citations

  • A high-performance silicon negative electrode active material and a preparation method thereof

    CN108963229A

  • Method of preparing anode slurry for secondary battery

    CN109075309A

  • Composite micron silicon material and preparation method and application thereof

    CN114314593A

  • Anode slurry for secondary battery

    WO2018095283A1